Secure Digital Signature Scheme Based on Elliptic Curves for Internet of Things - Sumanth Koppula; Jayabhaskar Muthukuru (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Advances in the info and communication knowledge have led to the emergence of Internet of things (IoT). Internet of things (loT) is worthwhile to members, trade, and society seeing that it generates a broad range of services by interconnecting numerous devices and information objects. Throughout the interactions among the many ubiquitous things, security problems emerge as noteworthy, and it is signiﬁcant to set up more suitable solution for security protection. Nonetheless, as loT devices have limited resource constraints to appoint strong protection mechanisms, they are vulnerable to sophisticated security attacks. For this reason, a sensible authentication mechanism that considers each useful resource constraints and safety is required. Our proposed scheme uses the standards of Elliptic Curve digital signature scheme and evaluates systematically the efficiency of our scheme and observes that our scheme with a smaller key size and lesser infrastructure performs on par with the prevailing schemes without compromising the security level.